ASSESSMENT OF ENVIRONMENTAL IMPACT OF SOLID WASTE DUMPSITES USING REMOTE SENSING (Nigerian Journal of Technology, 2017)
This study presents a remote sensing approach of using freely available Landsat 8 satellite Indicators (Land Surface Temperature (LST), Soil Adjusted Vegetation Index (SAVI)) and Shuttle Radar Topography Mission (SRTM) Digital Elevation Model (DEM) geospatial data to assess the impact of dumpsites on the environment in Benin City, Nigeria. The finding reveals that the average derived LST at the dumpsites were higher than the immediate surrounding, and the average SAVI values were lower than the immediate surrounding. The high values of LST at the dumpsites depict the effect of gases released because of decomposition activities, while low values of SAVI indicate vegetation response to soil and ground water contamination due to leachate infiltration. The average elevation within the dumpsite area derived from SRTM DEM was also applied as a proxy to estimate disposed waste quantity, and related closely with LST that depict biodegradation activities. The result presented here shows that bacterial and fungal counts correlate strongly with the LST and SAVI values at each of the dumpsites R2: LST vs Bacteria Count  = 0.982, LST vs Fungi Count = 0.951; SAVI vs Bacteria Count = 0.745, SAVI vs Fungi Count = 0.664, thereby suggesting remote sensing can be applied  to aid longterm dumpsite monitoring and management. http://dx.doi.org/10.4314/njt.v37i1.36